Iniciación, características y abandono del pandillaje juvenil en Lima - Javier, Jerjes Loayza (2019)
The article seeks to recognize the problems surrounding former gang members, frominterviews and life stories collected between 2013 and 2015. It delves into the speeches,motivations and more intimate experiences of young people, perceiving in family breakdown,rituals of collective effervescence, territorial defense and mutual inter group stigmatization asmain variables that allow us to understand the initiation and deterioration of gang violence.Finally, it is proposed as elements that keep members of the gang, first the possibility of seeingthemselves from a viewpoint of a generalized other more consensual, and secondly assimilatethe danger spreads about them that could end their lives or stigmatize perennially.